Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.cell.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Intron Removal Integrates Motivational State and Experience

Abstract: Myriad experiences produce transient memory, yet, contingent on the internal state of the organism and the saliency of the experience, only some memories persist over time. How experience and internal state influence the duration of memory at the molecular level remains unknown. A self-assembled aggregated state of Drosophila Orb2A protein is required specifically for long-lasting memory. We report that in the adult fly brain the mRNA encoding Orb2A protein exists in an unspliced non-protein-coding form. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 78 publications
2
46
0
Order By: Relevance
“…In this study, next-generation sequencing-based screening of the regulatory targets of nSBs identified a major molecular function of nSBs in promoting intron retention by more than 400 mRNAs during thermal stress recovery. In recent years, a number of studies have examined conditional intron retention in the nucleus and its biological functions, such as regulation of stress responses, the cell cycle, neuronal activity, learning and memory, spermiogenesis, and tumor growth (Boutz et al, 2015, Braun et al, 2017, Dominguez, Tsai et al, 2016, Gill, Park et al, 2017, Mauger et al, 2016, Naro, Jolly et al, 2017. Thus, nuclear intron retention is being accepted as a regulatory mechanism that fine tunes gene expression under various biological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, next-generation sequencing-based screening of the regulatory targets of nSBs identified a major molecular function of nSBs in promoting intron retention by more than 400 mRNAs during thermal stress recovery. In recent years, a number of studies have examined conditional intron retention in the nucleus and its biological functions, such as regulation of stress responses, the cell cycle, neuronal activity, learning and memory, spermiogenesis, and tumor growth (Boutz et al, 2015, Braun et al, 2017, Dominguez, Tsai et al, 2016, Gill, Park et al, 2017, Mauger et al, 2016, Naro, Jolly et al, 2017. Thus, nuclear intron retention is being accepted as a regulatory mechanism that fine tunes gene expression under various biological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies have examined conditional intron retention in the nucleus and its biological functions, such as regulation of stress responses, the cell cycle, neuronal activity, learning and memory, spermiogenesis, and tumor growth (Boutz et al, 2015;Dominguez et al, 2016;Mauger et al, 2016;Braun et al, 2017;Gill et al, 2017;Naro et al, 2017). In recent years, a number of studies have examined conditional intron retention in the nucleus and its biological functions, such as regulation of stress responses, the cell cycle, neuronal activity, learning and memory, spermiogenesis, and tumor growth (Boutz et al, 2015;Dominguez et al, 2016;Mauger et al, 2016;Braun et al, 2017;Gill et al, 2017;Naro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, next-generation sequencing-based screening of the regulatory targets of nSBs identified a major molecular function of nSBs in promoting intron retention by more than 400 mRNAs during thermal stress recovery. In recent years, a number of studies have examined conditional intron retention in the nucleus and its biological functions, such as regulation of stress responses, the cell cycle, neuronal activity, learning and memory, spermiogenesis, and tumor growth (Boutz et al, 2015;Dominguez et al, 2016;Mauger et al, 2016;Braun et al, 2017;Gill et al, 2017;Naro et al, 2017). Thus, nuclear intron retention is being accepted as a regulatory mechanism that fine-tunes gene expression under various biological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR was performed as described in Gill et.al [31] except random hexamer was used for cDNA synthesis. The following primers were used for DptB qPCR: 14 "ACTGGCATATGCTCCCAATTT" and "TCAGATCGAATCCTTGCTTTGG".…”
Section: Quantitative Pcrmentioning
confidence: 99%